NILAI-NILAI EDUKATIF SYAIR GULUNG SEBAGAI UPAYA PENDIDIKAN KEBENCANAAN BERBASIS KOMUNITAS PADA MASYARAKAT MELAYU DI KABUPATEN KETAPANG KALIMANTAN BARAT - Syaifulloh, Muhammad; Wibowo, Basuki (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2017)
This research aims to know and describe about 1) background of Syair Gulung in Ketapang Malay society of West Kalimantan, 2) Educative values contained in Syair Gulung, 3) Potential of Syair Gulung as a community-based disaster education efforts in Ketapang Malay society. This research uses qualitative research method with form of stuck case study strategy. Sources of data used are informants, places and events, and documents. Data collection techniques used direct observation techniques, in-depth interviews, and document studies. The sampling technique used is purposive sampling. Data validity uses triangulation and data analysis techniques using interactive analysis techniques.Syair Gulung is a typical Malay cultural art. The educational values that exist in the Syair Gulung can be developed as a tool of dissemination of disaster education which recently happened such as forest fire and flood. Natural disasters that occur in the Ketapang community can not be separated from the fading and shifting values of local wisdom that developed in the community. As a preventive form for the preservation of the natural environment, it reinvents the educational values implicit in Syair Gulung contributing greatly in the effort to preserve the nature of the disaster. Educational theories of local wisdom and disaster risk education are important in helping the realization of a disaster-conscious society. Community communities are highly effective targets for awareness of the importance of disaster education.